PROSPEK QANUN ACEH NO.6 TAHUN 2014 TENTANG UQUBAT TA’ZIR JARIMAH PEMERKOSAAN - Nairazi AZ (IAIN Langsa, 2019)
Regarding the prospect of Aceh’s Qanun Jinayat No. 6 Year 2014 about uqubat ta’zir jarimah of rape, there should be a cooperation between stakeholders and institution concerned in succeeding Aceh’s Qanun Jinayat, and the revision of uqubat ta’zir of rape by using a single system, in the form of the word “and” not the word “or” that is contained in article 48, 49, 50, to make the offenders obtain the multiple penalties, because the jarimah of rape must be severely punished. And for uqubat ta’zir jarimah of rape in Aceh’s Qanun Jinayat, if it is investigated further, there is no difference. In the present many academics and practitioners recommend that the rape penalty within criminal code (KUHP) should be revised because the punishment is considered ineffective to reduce and even solve the cases of rape in Indonesia.